Social Supply Chain: Five Lessons from a real world deployment - Wilding, Richard D.; Proctor, Robin (The Chartered Institute of Logistics and Transport, 2015)
Social networks are being increasingly utilised within supply chain management in order to enhance productivity, innovation and collaboration. It is increasingly recognised that for many supply chain environments, management by email is increasingly ineffective, with its linear chronological nature meaning that important issues can easily be lost.